Oklahoma! - Levien, Sonya, 1888?-1960.; Ludwig, William, 1912-1999.; Hornblow, Arthur, Jr., 1893-1976.; Zinnemann, Fred, 1907-1997.; MacRae, Gordon; Grahame, Gloria; Jones, Shirley, 1934 March 31-; Nelson, Gene, 1920-1996.; Steiger, Rod, 1925-2002.; Surtees, Robert; Ruggiero, Gene.; Rodgers, Richard, 1902-1979.; et al. (Beverly Hills, CA : Distributed by 20th Century Fox Home Entertainment, 1999)
MacRae portrays Curley, the handsome love-struck cowboy in love with Laura Williams (Jones). Steiger portrays the muscled hired hand who menaces them.
Aspect ratio 2.20:1.
"A Manga release."
"CBS Fox video"--Container.
"Originally produced on the stage by The Theatre Guild."
Adapted from Rodgers and Hammerstein's musical play which was based upon a dramatic play "Green grow the rushes" by Lynn Riggs.
Originally released as a motion picture in 1955; copyright renewed in 1983 by the Estate of Richard Rodgers and the Estate of Oscar Hammerstein, II.
Keywords: DVD-Video discs; Musicals; Musical films; Feature films; Films for the hearing impaired